The Influence Of Training, Competence, And Commitment On Employee Performance Mediated By Work Discipline At The Regional Personnel Agency Of Lumajang Regency - Nafsiyah, Wardatun; Cahyono, Dwi; Sanosra, Abadi (Jurnal Ekonomi, 2024)
Employee performance is a critical factor in determining organizational effectiveness and success, influenced by internal factors such as competence and commitment, and external factors like training. This study investigates the influence of training, competence, and employee commitment on employee performance, mediated by work discipline, at the Regional Personnel Agency of Lumajang Regency. Utilizing a causal-comparative approach, primary data was collected from 80 employees through questionnaires. The data was analyzed using Structural Equation Modeling (SEM-PLS) with the assistance of WarpPLS. The findings indicate that training, competence, and employee commitment significantly impact work discipline and employee performance. The mediating role of work discipline is confirmed as it enhances the relationship between training, competence, commitment, and performance. The study concludes that improving training programs, enhancing competence, and fostering employee commitment, coupled with a strong emphasis on work discipline, can lead to better employee performance and organizational effectiveness.